Walking as a Way of Experiencing Everyday Space - Gądecki, Jacek (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2011)
The paper constitutes the description of the reciprocal influence between man and space in the everyday experience. This bipolar relation makes everyday practice in the space an useful tool for the description of the contemporary times, and, at the same time, the way of criticise it. The text is using critical reflection on the space, understood in the popular and everyday categories, led from a perspective of the social science, mainly of sociology and social-cultural anthropology and indicates the potential of walking, as a method of of the everyday life and the social space.
Spacer jako forma doświadczenia przestrzeni codzienności
Keywords: urban anthropology; spatialization; everyday practice; walk